Survey of the UK veterinary profession: common species and conditions nominated by veterinarians in practice - Nielsen, T.D.; Dean, Rachel S.; Robinson, N.J.; Massey, A.; Brennan, Marnie L. (BMJ Publishing Group, 2014)
The practice of evidence-based veterinary medicine involves the utilisation of scientific evidence for clinical decision making. To enable this, research topics pertinent to clinical practice need to be identified, and veterinary clinicians are best placed to do this. The main aim of this study was to describe the veterinary population, the common species and conditions veterinary clinicians nominated they saw in practice and how much information clinicians perceived was available in the literature for these. A questionnaire was distributed to all Royal College of Veterinary Surgeons registered veterinarians agreeing to be contacted for research purposes (n=14,532). A useable response rate of 33 per cent (4842/14,532) was achieved. The most commonly seen species reported by vets were dogs, cats and rabbits followed by equines and cattle. Overall, skin conditions were most commonly mentioned for small animals, musculoskeletal conditions for equines and reproduction conditions for production animals. Veterinary clinicians perceived there was a higher level of information available in the literature for conditions in dogs, cattle and equines and lower levels for rabbits and guinea pigs. The results from this study can be used to help define the research needs of the profession to aid the incorporation of evidence in veterinary practice.